High-performance polar decoder for wireless sensor networks. (2nd December 2021) - Wang, Su-Fang
The Internet of Things (IoT) has promoted lots of advanced applications and become the hot topic for the development of next-generation networks. As an important part of IoT, low power and high reliability are the two crucial metrics when designing Wireless Sensor Networks (WSNs). In this paper, we propose a high-performance decoder for polar codes to improve the link reliability and transmission efficiency. We modify and optimise the original polar belief propagation decoding algorithms through investigating approximation and several types of factors. Moreover, the systematic coding of polar codes is utilised to further improve the error-correction performance by increasing acceptable encoding complexity. We conduct detailed experiments to demonstrate the low-complexity and high-performance advantages of proposed decoder. The improved robustness and low complexity of communication reduce the energy consumption and improving the information transmission reliability, which is suitable for the battery-operated low-complexity WSN applications.